Topography of violent intraspecific aggression in a subset of dogs from directionally selected lines of Canis familiaris - Victoria A. Cussen; Qinyi Lu; Pamela J. Reid (PLoS ONE, 2025)
We extended well-established animal models of human violence paradigms to domestic dogs ( Canis familiaris ) seized from organized dogfighting operations (n = 137). Using standard metrics of frequency, latency, duration, and severity of physical attack and social behavior, we found a pattern of severe intraspecific aggression and alterations in species typical social behavior comparable to that described in the models of violence literature. Behavior was coded from archival video footage of a model conspecific screening test by a technician blind to the categorical behavior severity rating assigned to the dogs on intake. Biting attacks were initiated with short latencies and a dramatically higher prevalence in dogs rated as severe for dog-directed aggression. Furthermore, high intensity attacks involving crushing and shearing bites and guttural growl vocalizations (a heretofore unreported vocalization) were exclusively exhibited by those subjects, and their attacks were directed to vulnerable body regions of the model, including the throat. Social investigation was absent or abbreviated; many individuals in this category failed to investigate the anogenital region of the model conspecific and spent a significantly smaller proportion of the test sniffing the model. Conversely, the comparator group from the same lines of domestic dogs showed normal social behavior toward the model conspecific despite their directional selection and life history. Our findings are the first to quantify the topography of extreme intraspecific aggression in domestic dogs, broadening our understanding of the social behavior of C. familiaris . In addition to contributing to basic science, our findings also support the use of expert ratings to categorize extreme intraspecific aggression in fight-bred lines. That finding is of applied value to shelter professionals making outcome decisions, and to legal professionals who require objective evidence grounded in accepted scientific paradigms when considering the prosecution of organized dogfighting cases.